Ipomoea stolonifera Fiddle-Leaf Morning Glory - Edward Gilman (EDIS)
This document provides an overview of the fiddle-leaf morning glory (Ipomoea stolonifera), an herbaceous vine native to the southeastern United States. It details the plant’s characteristics, including its rapid growth, glossy green leaves, and white funnel-shaped flowers. The fiddle-leaf morning glory is noted for its high drought and salt tolerance, making it well-suited for coastal landscapes as a ground cover or sand binder. The document also highlights its invasive potential and the need for frequent pruning due to its fast growth rate. Additionally, it discusses the plant’s adaptability to various soil types and its year-round planting suitability in USDA hardiness zones 8 through 11. Original publication date October 1999.